The Border War and American Liberty - Nicole Etcheson (Symphony in the Flint Hills, 2011)
Hanging in a corner of the Kansas state Capitol building in Topeka is John Steuart Curry’s mural “The Tragic Prelude.” A wild-eyed, bearded John Brown, arms out-stretched, clutches a Sharps rifle in one hand and the Bible in another.
Keywords: The Tragic Prelude; John Steuart Curry; John Brown; Civil War; Bleeding Kansas